Analisis Strategi Pemasaran Layanan Dalam Menghadapi Persaingan Bisnis Perusahaan Pengiriman (Studi Kasus: PT POS Indonesia KCU Bekasi) - Arraihan, Hilmi; Maulani, Syifa Fajar; Handayani, Melia (CV. ITTC INDONESIA, 2025)
PT Pos Indonesia is a state-owned enterprise (SOE) operating in postal and logistics services. In recent years, PT Pos Indonesia KCU Bekasi has experienced revenue fluctuations due to increasingly intense competition in the delivery service industry and the suboptimal implementation of its service marketing strategies. This condition requires the company to evaluate existing strategies and formulate effective service marketing strategies to maintain competitiveness and ensure business sustainability. Previous studies on delivery service marketing strategies tend to focus on partial analyses and have not comprehensively integrated SWOT and QSPM analyses, particularly at the level of main branch offices of PT Pos Indonesia. In addition, limited research combines qualitative and quantitative approaches to formulate service marketing strategies based on both internal and external organizational conditions. This study aims to describe the implementation of current service marketing strategies and to determine the most appropriate service marketing strategies for PT Pos Indonesia KCU Bekasi in facing business competition. This study employed a mixed method exploratory sequential approach with a descriptive research design. The population consisted of management personnel and customers of PT Pos Indonesia KCU Bekasi, with samples selected using purposive sampling techniques. Data were collected through interviews, observations, documentation studies, and questionnaires. Data analysis was conducted using the IFE, EFE, IE, SWOT, and QSPM matrices The results show that the IFE matrix score was 2.942 and the EFE matrix score was 2.968, placing the company in Cell V of the IE matrix, which indicates a hold and maintain strategy. The SWOT analysis positioned the company in Quadrant I, suggesting an SO strategy. Based on the QSPM analysis, the highest priority strategy was maintaining and strengthening relationships with customers, with a total attractiveness score of 6.748. The findings imply that strengthening customer relationships and optimizing internal strengths are key strategies to enhance the competitiveness of PT Pos Indonesia KCU Bekasi.